Universal Coverage on a Budget: Impacts on Health Care Utilization and Out-Of-Pocket Expenditures in Thailand - Supon Limwattananon; Sven Neelsen; Owen O'Donnell; Phusit Prakongsai; Viroj Tangcharoensathien; Eddy van Doorslaer (Tinbergen Institute, 2013)
We estimate the impact on health care utilization and out-of-pocket (OOP) expenditures of a major reform in Thailand that extended health insurance to one-quarter of the population to achieve universal coverage while keeping health spending below 4% of GDP. Identification is through comparison of changes in outcomes of groups to whom coverage was extended with those of public sector employees and their dependents whose coverage was not affected. The reform is estimated to have reduced the probability that a sick person goes without formal treatment by 3.2 percentage points (11%). It increased the probability of receiving public ambulatory care by 2.7 ppt (5%) and of admission to a public hospital by 1 ppt (18%). OOP expenditures were reduced by one-third on average, as was the probability of spending more than 10% of the household budget on health care, while spending at the very top of the OOP distribution was reduced by one-half representing substantial reductio ns in exposure to medical expenditure risk. Supply-side measures implemented with the coverage extension are likely to have helped realize these effects from an increased, but still very tight, budget.
urn:NBN:nl:ui:15-1765/40406
Keywords: H42; H51; I18; 330; Health Insurance; Health Care; Medical Expenditures; Universal Coverage; Thailand; Gesundheitsversorgung; Krankenversicherung; Gesundheitsfinanzierung; Thailand